2021
DOI: 10.3390/biom11111617
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of the Immunostimulatory Effect of Phosphodiester CpG Oligodeoxynucleotides by an Antiparallel Guanine-Quadruplex Structural Scaffold

Abstract: Guanine-quadruplex-based CpG oligodeoxynucleotides (G4 CpG ODNs) have been developed as potent immunostimulatory agents with reduced sensitivity to nucleases. We designed new monomeric G4 ODNs with an antiparallel topology using antiparallel type duplex/G4 ODNs as robust scaffolds, and we characterized their topology and effects on cytokine secretion. Based on circular dichroism analysis and quantification of mRNA levels of immunostimulatory cytokines, it was found that monomeric antiparallel G4 CpG ODNs conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Recently, we observed that apart from the hybrid, antiparallel G4 also exhibits high immunostimulatory activity, 27 indicating that G4 topology (the sequence of glycosidic bond angles within the quadruplex stem), 28 does not directly influence the TLR9 activation efficiency. The change in topology consequently results in a change in the folding manner of the loops connecting the G-quartets and charge distribution, which may be the factors directly influencing TLR9 activation.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Recently, we observed that apart from the hybrid, antiparallel G4 also exhibits high immunostimulatory activity, 27 indicating that G4 topology (the sequence of glycosidic bond angles within the quadruplex stem), 28 does not directly influence the TLR9 activation efficiency. The change in topology consequently results in a change in the folding manner of the loops connecting the G-quartets and charge distribution, which may be the factors directly influencing TLR9 activation.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Although G4-CpG ODNs are unmodified ODNs, they acquire resistance to nucleases because of their compact structure. As a result, compared to linear-CpG ODNs, G4-CpG ODNs showed excellent immunostimulatory activity in immune cells and mice [ 23 , 24 , 25 , 26 ]. The electrostatic interaction between the positively charged amino group on ε-PLL and the negatively charged phosphate group on G4-CpG ODN caused ODN condensation into the complexes.…”
Section: Resultsmentioning
confidence: 99%
“…In our previous studies, we developed a structured CpG ODN named the guanine-quadruplex (G4)-based CpG ODN [ 23 , 24 , 25 , 26 ]. The presence of guanine-rich regions in G4-CpG ODNs allows linear CpG ODNs to easily form G4 structures in the presence of potassium and sodium ions, resulting in high nuclease resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we reported that inserting CpG motifs into different loops of RE31, a sequence forming antiparallel G4 structure, leads to different immunostimulatory activities. Inserting the CpG motif into the first or third loop of RE31 preserves the anti-parallel structure of the wild-type, but the RE31 variant with CpG motifs in the third loop exhibits a significantly lower cytokine induction than the one with CpG motifs in the first loop 14 . The CpG motif located in the third loop of RE31 interacts with poly-guanine near the 3'-terminal and consequently forms a weaker interaction with TLR9 14 .…”
Section: Discussionmentioning
confidence: 97%